I am a Red Dress : Incantations on a Grandmother, a Mother, and a Daughter. - Camilleri, Anna (Arsenal Pulp Press, 2004)
In I Am a Red Dress, acclaimed writer and performer Anna Camilleri confronts the ghosts of her past as she seeks to find her rightful place in the world. Part memoir, part storytelling, Anna writes with passion and conviction about family and identity, and how the wounds of personal history can be healed through the imagination. These eloquent stories and narratives speak to the heart of three generations of womenAnna, her mother, and her grandmotheras they dealt with a cycle of family abuse; in them, the red dress appears as a symbol of defiance and empowerment. Throughout the book, Anna un.